Current evidence for avoidant restrictive food intake disorder: Implications for clinical practice and future directions - Tanith Archibald; Rachel Bryant‐Waugh (Wiley, 2023)
Abstract Background ARFID (avoidant restrictive food intake disorder) is a relatively new diagnostic term covering a number of well‐recognised, clinically significant disturbances in eating behaviour unrelated to body weight/shape concerns. Its phenotypic heterogeneity combined with much about the condition remaining unknown, can contribute to uncertainties about best practice. While other reviews of the evidence base for ARFID exist, few specifically target health care professionals and implications for clinical practice. Methods A narrative review was conducted to synthesise the findings of ARFID papers in scientific journals focussing on four key areas relevant to clinical practice: prevalence, assessment and characterisation of clinical presentations, treatment, and service delivery. Freely available online databases were searched for case studies and series, research reports, review articles, and meta‐analyses. Findings were reviewed and practice implications considered, resulting in proposed clinical recommendations and future research directions. Results We discuss what is currently known about the four key areas included in this review. Based on available evidence as well as gaps identified in the literature, recommendations for clinical practice are derived and practice‐related research priorities are proposed for each of the four of the areas explored. Conclusion Prevalence studies highlight the need for referral and care pathways to be embedded across a range of health care services. While research into ARFID is increasing, further studies across all areas of ARFID are required and there remains a pressing need for guidance on systematic assessment, evidence‐based management, and optimal service delivery models. Informed clinical practice is currently predominantly reliant on expert consensus and small‐scale studies, with ongoing routine clinical data capture, robust treatment trials and evaluation of clinical pathways all required. Despite this, a number a positive practice points emerge.